Effects of windbreak Forest according to tree species and planting methods based on wind tunnel experiments - Seong-Hun Jeong; Sang-Hyun Lee (Forest Science and Technology, 2020)
To provide a basis for the effective and efficient design of windbreak forests, wind tunnel tests were conducted to analyze the protection against wind afforded by the use of various species and various structures of planted trees. Various row-based planting structures were used in an attempt to find the most effective arrangement of a windbreak forest. Four types of structures were studied: a simple structure of coniferous trees (1, 2, or 3 rows of Pinus thunbergii), a simple structure of broadleaf trees (1, 2, or 3 rows of Quercus acutissima), mixed structure 1 (3 rows: P. thunbergii, Q. acutissima and P. thunbergii) and mixed structure 2 (3 rows: Q. acutissima, P. thunbergii and Q. acutissima). The testing materials were 3-year-old P. thunbergii and 8-year-old Q. acutissima. As the height of the testing part was 2.0 m, the height of trees was cut to make it 1.5 m based. The trees were fixed in a vase of 30 cm (Width) × 30 cm (Height). The experimental simulation model was designed 3meter (Width) × 2meter (Height) × 9 meter (Length). Putting porosity between trees aside, it was appropriate with the 7.5% of black ratio. All arrangements of P. thunbergii rows decreased the wind speed at every measurement point; especially, the 3-row structure of P. thunbergii showed a wind speed reduction of more than 15% greater than the two single-row structures studied. The wind speed reduction of P. thunbergii was maximized at a distance 1 m downwind from the last row, with wind speed increasing further downwind. Also, comparing the effect of decreasing wind speed according to the height in one-layered structure, middle-height marked the best decrease and lowered as it goes far from the middle-height. This can be explained with the cone-shaped water pipe. However, observing that the same phenomenon does not happen in three-layered structures, it was found that the difference due to different shapes of the water pipe can be offset by adding a row of plants. Therefore, using the alternating structure of coniferous, broadleaf, and coniferous rows would be a better choice, offering a similar effect with less risk of loss to disease and insects.